A kind of leaching resin and preparation method thereof and preparation method of high-purity cobalt
By polymerizing acidic phosphorus and ammonia extractants in situ on styrene-divinylbenzene macroporous copolymer, a good stability of extract resin was prepared, and the separation and purification of high-purity cobalt was achieved through adsorption, rinsing and desorption processes were adopted to achieve the solution. The problems of complex preparation methods for high-purity cobalt and poor purification effects in the prior art are achieved, and high-efficiency preparation and low-cost process of high-purity cobalt are realized.
Patent Information
- Application Number
- CN202311336876.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-10-17
AI Technical Summary
The existing high-purity cobalt preparation methods have problems such as complex treatment methods and poor purification effects, and it is difficult to effectively remove key impurities such as Ni, Fe, Cu, etc., and the stability and cost of the extractant are relatively high.
Using styrene-diethylene benzene macroporous copolymer as carrier, in situ polymerizes acidic phosphorus extractant and ammonia extractant to prepare a good stability extract resin, and achieve high purity cobalt through adsorption, rinsing and desorption processes Separation and purification, simple process and low cost.
The purity of high-purity cobalt is achieved above 5N, the process flow is simple, the reagent consumption is small, and the leaching resin can be reused, reducing the cost of separation and purification, and the purity can reach more than 99.9995%.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrometallurgy, and in particular to a leaching resin and a preparation method thereof, and a preparation method of high-purity cobalt. Background Art
[0002] High-purity metals play an important role in the field of integrated circuits. my country is in urgent need of high-purity cobalt materials with a purity of more than 99.999% (5N). The most harmful key impurities in large-scale integrated circuits are Ni, Fe, Cu and other elements. The limits of the above impurity elements in the integrated circuit industry at home and abroad have been reduced to below ppm. Therefore, the difficulty in the preparation of high-purity cobalt is mainly to overcome the impurity removal technology of key impurities such as Ni, Fe, Cu and other elements.
[0003] Chinese patent CN200810118065.0 discloses a process for extracting and purifying a cobalt solution by separation and purification by chromatography, wherein leaching resin CL-P507 is used as a separation agent and HAc-NaAc buffer solution is used as an eluent, and cobalt with a purity of 99.99% can be obtained. However, in the leaching resin CL-P507 used in this method, the extractant P507 is adsorbed on the macroporous resin by saponification adsorption, and the extractant is easily eluted during delamination, and the stability needs to be strengthened. In addition, the purity of cobalt obtained by this patent is 99.99%, which does not reach above 5N. Chinese patent CN202111439462.X discloses a method for preparing high-purity cobalt, wherein one or more of ammonium hydrogen sulfide, hydrogen sulfide, ammonia gas, and ammonia water are added as precipitants to remove impurities in the cobalt solution, and high-purity cobalt salt is obtained after filtration. However, this method uses a precipitant to remove impurities, and the selectivity is not high, and it is difficult to obtain a high-purity cobalt solution. Chinese patent CN202211303507.5 discloses a method for preparing cobalt sulfate electrolyte for ultra-high purity cobalt. The patent uses at least one chelating resin and at least one ion exchange resin to deeply remove impurities from the cobalt sulfate stock solution. After purification, the content of Fe, Ni, and Cu in the solution is less than 0.005 mg / L. However, the method uses chelating resin, which is expensive, and requires the use of two resin columns, and the separation process is long.
[0004] In summary, the current preparation methods of high-purity cobalt in this field all have the problems of complex processing methods and poor purification effects, and the purification technology of cobalt still needs further exploration and improvement. Summary of the invention
[0005] In view of this, the present invention provides a leaching resin and a preparation method thereof and a preparation method of high-purity cobalt. The leaching resin provided by the present invention has good stability, and the cobalt can be separated and purified by using the leaching resin, and only adsorption, elution and desorption are required, the operation is simple, the cost is low, and the purity of the obtained high-purity cobalt can reach above 5N.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A leaching resin comprises a styrene-divinylbenzene macroporous copolymer and a composite extractant in-situ polymerized on the styrene-divinylbenzene macroporous copolymer, wherein the composite extractant comprises an acidic phosphorus extractant and an ammonia extractant.
[0008] Preferably, the acidic phosphorus extractant comprises one or more of di(2-ethylhexyl)phosphoric acid, 2-ethylhexylphosphonic acid mono-(2-ethylhexyl) ester and di(2,4,4-trimethylpentyl)phosphonic acid;
[0009] The ammonia extractant includes one or more of tri(octyl-decyl)alkyl tertiary amine, secondary carbon primary amine extractant and trioctylmethylammonium chloride.
[0010] Preferably, the particle size of the leaching resin is 48 to 1700 μm.
[0011] The present invention also provides a method for preparing the leaching resin described in the above scheme, comprising the following steps:
[0012] mixing water, gelatin, ammonium thiocyanate and a surfactant to obtain an aqueous phase;
[0013] Mixing styrene, divinylbenzene and an initiator to obtain an oil phase;
[0014] The oil phase and the water phase are mixed to react, and after the resin is spherical, a composite extractant is added to carry out in-situ polymerization reaction to obtain the leaching resin.
[0015] Preferably, the volume ratio of styrene to divinylbenzene is 100:(1-100); the ratio of the total volume of styrene and divinylbenzene to the volume of the composite extractant is 100:(10-120);
[0016] The surfactant includes one or more of polyvinyl alcohol, hydroxymethyl cellulose and TX-100.
[0017] Preferably, the in-situ polymerization reaction comprises a first stage and a second stage performed sequentially, wherein the temperature of the first stage is 70-85°C and the time is 0.5-3h, and the temperature of the second stage is 80-95°C and the time is 0.3-1h.
[0018] The present invention also provides a method for preparing high-purity cobalt, comprising the following steps:
[0019] Adsorbing the cobalt-containing acidic solution with a leaching resin to obtain a cobalt-loaded resin; the leaching resin is the leaching resin described in the above scheme or the leaching resin prepared by the preparation method described in the above scheme;
[0020] The cobalt-loaded resin is sequentially eluted and desorbed to obtain a cobalt-containing desorption liquid; the purity of cobalt in the cobalt-containing desorption liquid is greater than or equal to 99.999%.
[0021] Preferably, the cobalt-containing acidic solution is prepared from a cobalt-containing compound and an acid; the acid is one or more of nitric acid, hydrochloric acid, sulfuric acid, formic acid and acetic acid; and the pH value of the cobalt-containing acidic solution is 2-6.
[0022] Preferably, the eluting agent used for elution is a low-concentration acid; the concentration of the low-concentration acid is 0.01-1 mol / L; the low-concentration acid is one or more of nitric acid, formic acid and acetic acid.
[0023] Preferably, the desorbent for desorption is a high-concentration acid; the concentration of the high-concentration acid is 0.5-6 mol / L; the high-concentration acid is one or more of nitric acid, formic acid and acetic acid.
[0024] The present invention provides a leaching resin, comprising a styrene-divinylbenzene macroporous copolymer and a composite extractant in situ polymerized on the styrene-divinylbenzene macroporous copolymer, wherein the composite extractant comprises an acidic phosphorus extractant and an ammonia extractant. In the leaching resin provided by the present invention, the composite extractant is in situ polymerized on the styrene-divinylbenzene macroporous copolymer, and the extractant is tightly combined with the polymer skeleton of the resin (i.e., the styrene-divinylbenzene macroporous copolymer), is not easy to fall off, and has good stability.
[0025] The present invention also provides a method for preparing the leaching resin described in the above scheme. The present invention adopts emulsion suspension polymerization to prepare the leaching resin, and the composite extractant can be in situ composited on the polymer skeleton while forming the polymer skeleton. The preparation method is simple, convenient for large-scale preparation, and has a high resin yield.
[0026] The present invention also provides a method for preparing high-purity cobalt, comprising the following steps: using a leaching resin to adsorb a cobalt-containing acidic solution to obtain a loaded cobalt resin; eluting and desorbing the loaded cobalt resin in sequence to obtain a cobalt-containing desorption liquid; the purity of cobalt in the cobalt-containing desorption liquid is greater than or equal to 99.999%. The leaching resin of the present invention is used to separate and purify cobalt, and high-purity cobalt with a purity of more than 5N can be obtained through only three steps of adsorption, eluting, and desorption. The process flow is simple, the reagent consumption is small, and the leaching resin can be reused after desorption, further reducing the cost of separation and purification. Experimental results show that the purity of cobalt in the cobalt-containing desorption liquid obtained by the present invention can reach more than 99.9995%. DETAILED DESCRIPTION
[0027] The invention provides a leaching resin, comprising a styrene-divinylbenzene macroporous copolymer and a composite extractant in-situ polymerized on the styrene-divinylbenzene macroporous copolymer, wherein the composite extractant comprises an acidic phosphorus extractant and an ammonia extractant.
[0028] In the present invention, the acidic phosphorus extractant preferably includes one or more of di(2-ethylhexyl)phosphoric acid (P204), 2-ethylhexylphosphonic acid mono-(2-ethylhexyl) ester (P507) and di(2,4,4-trimethylpentyl)phosphonic acid (Cyanex272); the ammonia extractant preferably includes one or more of tri(octyl-decyl)alkyl tertiary amine (N235), secondary carbon primary amine extractant (N1923) and trioctylmethylammonium chloride (N263); the volume ratio of the acidic phosphorus extractant to the ammonia extractant is preferably (8-9.5):(0.5-2), more preferably 9:1. In the present invention, the leaching resin is prepared by suspension polymerization, which will be described in detail in the preparation method section later.
[0029] In the present invention, the particle size of the leaching resin is preferably 48 to 1700 μm, more preferably 75 to 150 μm.
[0030] The present invention also provides a method for preparing the leaching resin described in the above scheme, comprising the following steps:
[0031] mixing water, gelatin, ammonium thiocyanate and a surfactant to obtain an aqueous phase;
[0032] Mixing styrene, divinylbenzene and an initiator to obtain an oil phase;
[0033] The oil phase and the water phase are mixed to react, and after the resin is spherical, a composite extractant is added to carry out in-situ polymerization reaction to obtain the leaching resin.
[0034] The present invention has no particular limitation on the sources of all raw materials, and any commercially available raw materials may be used.
[0035] The present invention mixes water, gelatin, ammonium thiocyanate and a surfactant to obtain an aqueous phase. In the present invention, the surfactant preferably includes one or more of polyvinyl alcohol, hydroxymethyl cellulose and TX-100; the gelatin and the surfactant can reduce the interfacial tension of the liquid, so that the dispersion degree of the monomer droplets is higher, and can also increase the viscosity of the polymerization medium, thereby hindering the collision and bonding between the monomer droplets, and can also form a protective film on the surface of the monomer droplets to prevent the droplets from condensing.
[0036] In the present invention, the concentration of gelatin in the aqueous phase is preferably 0.005-0.02 g / mL, more preferably 0.01-0.015 g / mL; the mass ratio of ammonium thiocyanate to gelatin is preferably 1:(5-20), more preferably 1:(8-15), and even more preferably 1:10; the volume fraction of the surfactant in the aqueous phase is preferably 0.01%-0.1%.
[0037] The present invention mixes styrene, divinylbenzene and an initiator to obtain an oil phase. In the present invention, the volume ratio of styrene to divinylbenzene is preferably 100:(1-100), more preferably 100:(20-80), more preferably 100:(40-60), and most preferably 100:50; the present invention has no special requirements for the initiator, and an initiator well known to those skilled in the art can be used. In a specific embodiment of the present invention, the initiator is preferably peroxide and / or persulfate, more preferably one or more of hydroxydiisopropylbenzene peroxide, benzoyl peroxide and potassium persulfate, and more preferably benzoyl peroxide. acyl; the concentration of the initiator in the oil phase is preferably 0.001-0.01 g / mL, more preferably 0.003-0.008 g / mL, and more preferably 0.004-0.006 g / mL; the type and ratio of the composite extractant are the same as those in the above scheme and will not be repeated here; the ratio of the total volume of styrene and divinylbenzene to the volume of the composite extractant is preferably 100:(10-120), more preferably 100:(50-120), more preferably 100:(80-120), and most preferably 100:100.
[0038] In a specific embodiment of the present invention, styrene and divinylbenzene are preferably added to a separatory funnel, then washed twice with sodium hydroxide aqueous solution, and then the washed mixture is washed with water until neutral, and then an initiator is added to obtain an oil phase; the concentration of the sodium hydroxide aqueous solution is preferably 1 mol / L; the ratio of the volume of the sodium hydroxide aqueous solution used for a single wash to the total volume of the styrene and divinylbenzene is preferably 133:400; the washing is preferably: adding the sodium hydroxide aqueous solution to a separatory funnel, separating after shaking, and discarding the aqueous phase.
[0039] After obtaining the water phase and the oil phase, the present invention mixes the oil phase and the water phase for reaction, and after the resin is spherical, a composite extractant is added to carry out in-situ polymerization reaction to obtain the leaching resin. In the present invention, the volume ratio of the water phase to the oil phase is preferably (2-10):1, more preferably (3-8):1; in a specific embodiment of the present invention, since gelatin is not easily soluble in water, it is preferred to heat the water phase first until the gelatin is completely dissolved, and then slowly add the oil phase under stirring; the heating temperature is preferably 50°C.
[0040] In the present invention, the temperature for the reaction of the oil phase and the water phase is preferably 70-85°C; in a specific embodiment of the present invention, after the addition of the oil phase is completed, the temperature of the mixture is preferably raised to 70-85°C for reaction, the reaction progress is observed, and when the resin is just balled, a composite extractant is added to the system for in-situ polymerization. In the present invention, the in-situ polymerization reaction preferably includes a first stage and a second stage carried out in sequence, the temperature of the first stage is preferably 70-85°C, the time is preferably 0.5-3h, and the temperature of the second stage is preferably 80-95°C, and the time is preferably 0.3-1h.
[0041] After the in-situ polymerization reaction is completed, the present invention preferably screens and dries the obtained product to obtain the leaching resin; the mesh size of the sieve used for screening is preferably 10 to 300 meshes, more preferably 100 to 200 meshes; the drying method is preferably air-drying; in a specific embodiment of the present invention, the screened resin is preferably washed with water and then dried.
[0042] The present invention adopts a suspension polymerization method to prepare the leaching resin, and can form a polymer skeleton while making the composite extractant in situ composited on the polymer skeleton, so that the two are tightly combined and not easy to fall off, the preparation process is simple, it is convenient for mass preparation, and the resin yield is high.
[0043] The present invention also provides a method for preparing high-purity cobalt, comprising the following steps:
[0044] Adsorbing the cobalt-containing acidic solution with a leaching resin to obtain a cobalt-loaded resin; the leaching resin is the leaching resin described in the above scheme or the leaching resin prepared by the preparation method described in the above scheme;
[0045] The cobalt-loaded resin is sequentially eluted and desorbed to obtain a cobalt-containing desorption liquid; the purity of cobalt in the cobalt-containing desorption liquid is greater than or equal to 99.999%.
[0046] The present invention uses leaching resin to adsorb the cobalt-containing acidic solution to obtain a loaded cobalt resin. In the present invention, the cobalt-containing acidic solution is preferably prepared from a cobalt-containing compound and an acid; the acid is preferably one or more of nitric acid, hydrochloric acid, sulfuric acid, formic acid and acetic acid; the pH value of the cobalt-containing acidic solution is preferably 2 to 6, more preferably 3 to 5; the cobalt-containing compound is preferably one or more of cobalt nitrate, cobalt carbonate, cobalt hydroxide, cobalt oxide and cobalt oxalate; when the cobalt-containing compound is cobalt oxalate, the cobalt oxalate is preferably calcined and decomposed into cobalt oxide, and then prepared with an acid. The concentration of cobalt in the cobalt-containing acidic solution is preferably 10 to 150 g / L.
[0047] In a specific embodiment of the present invention, the cobalt-containing compound can be directly dissolved with acid, or the cobalt-containing compound can be first dissolved in water and then adjusted to a pH value of 2-6 with acid.
[0048] In the present invention, before the adsorption, the leaching resin is preferably saponified with ammonia water, and the concentration of the ammonia water used is preferably 1-13 mol / L, more preferably 5-10 mol / L; the saponification degree of the saponification is preferably 30-100%, more preferably 60-95%; the adsorption method is preferably dynamic adsorption; the present invention preferably packs the leaching resin into a column to obtain a separation column, and then passes the cobalt-containing acidic solution through the separation column for adsorption; the end point of the adsorption is preferably based on the concentration of cobalt in the outflowing adsorption tail liquid reaching 0.1-10 g / L, more preferably 1 g / L.
[0049] After obtaining the loaded cobalt resin, the present invention sequentially performs elution and desorption on the loaded cobalt resin to obtain a cobalt-containing desorption liquid; the purity of cobalt in the cobalt-containing desorption liquid is greater than or equal to 99.999%. In the present invention, the elution agent for elution is a low-concentration acid; the concentration of the low-concentration acid is preferably 0.01 to 1 mol / L, more preferably 0.1 to 0.5 mol / L; the low-concentration acid is preferably one or more of nitric acid, formic acid and acetic acid, more preferably nitric acid with a concentration of 0.1 to 0.5 mol / L or formic acid with a concentration of 0.1 to 0.5 mol / L. In a specific embodiment of the present invention, it is preferred that the above-mentioned low-concentration acid is passed through the separation column after adsorption for elution; the present invention removes the cobalt-containing acidic solution that is not adsorbed on the surface of the leaching resin by elution, and can remove some impurity ions at the same time. The eluent obtained by elution contains part of the cobalt element. The present invention preferably uses the eluent as the raw material liquid to continue the adsorption step; in a specific embodiment of the present invention, it is preferred to connect the separation column after adsorption (recorded as 1# separation column) in series with another separation column without adsorption (recorded as 2# separation column), and then introduce the eluent from the inlet end of the 1# separation column, and collect the eluent from the end of the 2# separation column. During the elution process, the cobalt concentration in the eluent first increases and then decreases. When the cobalt concentration in the outflowing eluent first increases and then decreases to 0.01-0.5 g / L, more preferably 0.1 g / L, the elution is completed; after the elution is completed, the present invention preferably transfers the feed port of the cobalt-containing feed liquid to the 2# separation column, and reuses it when the next batch of cobalt is loaded until the cobalt adsorption in the 2# separation column is saturated. After the cobalt adsorption in the 2# separation column is saturated, elution and desorption can be carried out according to the same method.
[0050] After elution, the present invention desorbs the eluted leaching resin (i.e., the 1# separation column), and the desorbent for desorption is preferably a high-concentration acid; the concentration of the high-concentration acid is preferably 0.5-6 mol / L, more preferably 1-5 mol / L; the high-concentration acid is preferably one or more of nitric acid, formic acid and acetic acid, more preferably nitric acid; the high-concentration acid is preferably prepared using high-grade pure acid; in a specific embodiment of the present invention, it is preferred to directly flow the desorbent through the eluted separation column for desorption, and the end point of the desorption is preferably based on the concentration of cobalt in the outflowing desorption liquid being less than 0.1 g / L. After desorption is completed, the desorbed leaching resin is preferably saponified with high-purity ammonia water and reused; the concentration of ammonia water is preferably 1-13 mol / L, more preferably 5-10 mol / L; the saponification degree of the saponification is preferably 30-100%, more preferably 60-95%.
[0051] In the present invention, the purity of cobalt in the cobalt-containing desorption solution obtained by desorption is greater than or equal to 99.999%. In a specific embodiment of the present invention, the cobalt-containing desorption solution can be directly evaporated and crystallized to obtain a high-purity cobalt salt solid; or oxalic acid is added to the cobalt-containing desorption solution to precipitate cobalt oxalate, which is then calcined to obtain high-purity cobalt oxide.
[0052] The invention adopts leaching resin to separate and purify cobalt, and a desorption liquid containing high-purity cobalt can be obtained only through adsorption, elution and desorption, and the process flow is simple and the reagent consumption is small; moreover, the composite extractant in the leaching resin is not easy to fall off from the styrene-divinylbenzene copolymer, and the leaching resin can be reused after desorption, thereby reducing the cost of separation and purification.
[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] Example 1
[0055] (1) 3000 mL of pure water, 36 g of gelatin, 3.6 g of ammonium thiocyanate and 1 mL of TX-100 were added to a 5 L reactor in sequence and heated to 50° C. in a water bath under mechanical stirring. After the gelatin was completely dissolved, an aqueous phase was obtained.
[0056] Add 300 mL of styrene and 100 mL of 55% divinylbenzene to a pear-shaped separatory funnel, mix well, then add 133 mL of 1 mol / L sodium hydroxide aqueous solution, shake for 5 min, let stand for phase separation and discard the aqueous solution, then repeat washing once with the same phase ratio, then wash the purified styrene-divinylbenzene with pure water until neutral, then add 3.6 g of benzoyl peroxide and mix well to obtain the oil phase.
[0057] 360 mL of Cyanex 272 and 40 mL of N235 were mixed to prepare a composite extractant.
[0058] Under stirring, the oil phase was slowly added to the water phase. After the oil phase was added, the water bath temperature was raised to 80°C, and the resin synthesis process was observed. When the resin was balled, the composite extractant was added dropwise, and the reaction was carried out at a constant temperature for 2 hours. The water bath temperature was then raised to 90°C and kept warm for 0.5 hours. The light yellow spheres obtained by wet screening (particle size greater than 100 mesh) were washed with pure water, and then filtered and the product was air-dried to obtain 550g of leaching resin. Six batches of synthesis were carried out to obtain a total of 3080g of leaching resin.
[0059] (2) Take 300 g of cobalt nitrate, add 1 L of high-purity water, continue heating and stirring until it is completely dissolved, filter, measure the cobalt concentration in the filtrate, and then adjust the cobalt concentration and acidity in the filtrate to obtain a cobalt-containing acidic solution with a cobalt concentration of 95.24 g / L and pH = 5.0.
[0060] (3) 500 g of the leaching resin synthesized in (1) was respectively loaded into the 1# column and the 2# column, and saponified with ammonia water, the concentration of which was 6 mol / L and the saponification degree was 95%. Then, the cobalt-containing acidic solution obtained in (2) was passed through the 1# column at a flow rate of 15 mL / min using a plunger pump, and the cobalt concentration in the effluent was monitored every 5 min. When the cobalt concentration in the effluent reached 1 g / L, the addition of the cobalt-containing acidic solution was stopped, thereby obtaining a cobalt-loaded separation column.
[0061] (4) The cobalt-loaded separation column obtained in (3) was connected in series with the No. 2 column, and washing acid (nitric acid with a concentration of 0.5 mol / L) was introduced into the inlet of the cobalt-loaded separation column and discharged from the outlet of the No. 2 column at a flow rate of 15 mL / min to elute the cobalt-loaded separation column. The concentration of cobalt in the eluent discharged was monitored by sampling every 5 minutes. When the concentration of cobalt therein first increased and then decreased to 0.3 g / L, the addition of washing acid was stopped. Then, 3 mol / L high-grade pure nitric acid was used as a desorbent to desorb the washed cobalt-loaded separation column at a flow rate of 10 mL / min. When the concentration of cobalt in the desorbent discharged was lower than 0.1 g / L, the introduction of desorbent was stopped to obtain a cobalt-containing desorbent and a leaching resin column after desorption. The purity of cobalt in the obtained cobalt-containing desorbent was 99.9998%.
[0062] Example 2
[0063] (1) The cobalt-containing acidic solution prepared in Example 1 was passed through the desorbed leaching resin column in Example 1 (the desorbed leaching resin in Example 1 was reused after being saponified with high ammonia water, the concentration of the ammonia water used was 1 mol / L, and the saponification degree was 60%) by using a plunger pump at a flow rate of 100 mL / min, and the cobalt concentration in the effluent was monitored every 1 min. When the cobalt concentration in the effluent reached 0.01 g / L, the addition of the cobalt-containing acidic solution was stopped to obtain a cobalt-loaded separation column.
[0064] (2) The cobalt-loaded separation column obtained in (1) was connected in series with the No. 2 column after elution in Example 1, and washing acid (formic acid with an acidity of 0.1 mol / L) was introduced from the inlet end of the cobalt-loaded separation column and discharged from the outlet end of the No. 2 column at a flow rate of 15 mL / min to elute the cobalt-loaded separation column. The concentration of cobalt in the eluent discharged was monitored by sampling every 5 minutes. When the concentration of cobalt therein first increased and then decreased to 0.05 g / L, the addition of washing acid was stopped. Then, 5 mol / L formic acid was used as a desorbent at a flow rate of 10 mL / min to desorb the washed cobalt-loaded separation column. When the concentration of cobalt in the desorbent discharged was lower than 0.01 g / L, the introduction of desorbent was stopped to obtain a cobalt-containing desorbent and a desorbed leaching resin column. The purity of cobalt in the obtained cobalt-containing desorbent was 99.9998%.
[0065] Example 3
[0066] (1) The cobalt-containing acidic solution prepared in Example 1 was passed through the desorbed leaching resin column in Example 2 using a plunger pump at a flow rate of 1 mL / min (the desorbed leaching resin in Example 2 was saponified with high-purity ammonia water and reused, the concentration of ammonia water used for saponification was 10 mol / L, and the degree of saponification was 90%), and the cobalt concentration in the effluent was monitored every 30 min. When the cobalt concentration in the effluent reached 0.01 g / L, the addition of the cobalt-containing acidic solution was stopped to obtain a cobalt-loaded separation column.
[0067] (2) The cobalt-loaded separation column obtained in (1) was connected in series with the No. 2 column after elution in Example 2, and washing acid (nitric acid with an acidity of 1.0 mol / l) was introduced from the inlet end of the cobalt-loaded separation column and discharged from the outlet end of the No. 2 column at a flow rate of 1 mL / min to elute the cobalt-loaded separation column. The concentration of cobalt in the effluent eluent was monitored by sampling every 30 min. When the concentration of cobalt therein first increased and then decreased to 0.3 g / L, the addition of washing acid was stopped. Then, hydrochloric acid solution with a pH of 1 was used as a desorbent to desorb the washed cobalt-loaded separation column at a flow rate of 1 mL / min. When the concentration of cobalt in the effluent desorbent was lower than 0.01 g / L, the introduction of desorbent was stopped to obtain a cobalt-containing desorbent and a leaching resin column after desorption. The purity of cobalt in the obtained cobalt-containing desorbent was 99.9996%.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A leaching resin, characterized in that: The invention comprises a styrene-divinylbenzene macroporous copolymer and a composite extractant in-situ polymerized on the styrene-divinylbenzene macroporous copolymer, wherein the composite extractant comprises an acidic phosphorus extractant and an ammonia extractant; the acidic phosphorus extractant comprises one or more of di(2-ethylhexyl)phosphoric acid, 2-ethylhexylphosphonic acid mono-(2-ethylhexyl) ester and di(2,4,4-trimethylpentyl)phosphonic acid; the ammonia extractant comprises one or more of tri(octyl-decyl)alkyl tertiary amine, secondary carbon primary amine extractant and trioctylmethylammonium chloride.
2. The leaching resin according to claim 1, characterized in that The particle size of the leaching resin is 48 to 1700 μm.
3. The method for preparing the leaching resin according to any one of claims 1 to 2, characterized in that: The following steps are involved: mixing water, gelatin, ammonium thiocyanate and a surfactant to obtain an aqueous phase; Mixing styrene, divinylbenzene and an initiator to obtain an oil phase; The oil phase and the water phase are mixed to react, and after the resin is spherical, a composite extractant is added to carry out in-situ polymerization reaction to obtain the leaching resin.
4. The preparation method according to claim 3, characterized in that: The volume ratio of the styrene to divinylbenzene is 100:(1-100); the ratio of the total volume of the styrene and divinylbenzene to the volume of the composite extractant is 100:(10-120); The surfactant includes one or more of polyvinyl alcohol, hydroxymethyl cellulose and TX-100.
5. The preparation method according to claim 3, characterized in that: The in-situ polymerization reaction comprises a first stage and a second stage, wherein the temperature of the first stage is 70-85° C. and the time is 0.5-3 h, and the temperature of the second stage is 80-95° C. and the time is 0.3-1 h.
6. A method for preparing high-purity cobalt, characterized in that: The following steps are involved: Adsorbing the cobalt-containing acidic solution with a leaching resin to obtain a cobalt-loaded resin; the leaching resin is the leaching resin according to any one of claims 1 to 2 or the leaching resin prepared by the preparation method according to any one of claims 3 to 5; The cobalt-loaded resin is sequentially eluted and desorbed to obtain a cobalt-containing desorption liquid; the purity of cobalt in the cobalt-containing desorption liquid is greater than or equal to 99.999%.
7. The preparation method according to claim 6, characterized in that: The cobalt-containing acidic solution is prepared from a cobalt-containing compound and an acid; the acid is one or more of nitric acid, hydrochloric acid, sulfuric acid, formic acid and acetic acid; and the pH value of the cobalt-containing acidic solution is 2-6.
8. The preparation method according to claim 6, characterized in that: The eluting agent used for elution is a low-concentration acid; the concentration of the low-concentration acid is 0.01-1 mol / L; the low-concentration acid is one or more of nitric acid, formic acid and acetic acid.
9. The preparation method according to claim 6, characterized in that: The desorbent for desorption is a high-concentration acid; the concentration of the high-concentration acid is 0.5-6 mol / L; the high-concentration acid is one or more of nitric acid, formic acid and acetic acid.
Citation Information
Patent Citations
Process method for separating and purifying cobalt solution by extraction chromatography
CN101643859B
A method for preparing high-purity cobalt and its application
CN114192792B
Preparation method of cobalt sulfate electrolyte for ultra-pure cobalt
CN115627499A
Elution-extracting resin using amide compound as extracting agent and preparation method thereof
CN101139418A
Polymer beads containing an immobilized extractant for sorbing metals from solution
US5279745A